Determining standardized causes of death of infants, children, and adolescents living with HIV in Asia. (1st August 2020) - Sohn, Annette H.; Lumbiganon, Pagakrong; Kurniati, Nia; Lapphra, Keswadee; Law, Matthew; Do, Viet C.; Van Nguyen, Lam; Truong, Khanh H.; Wati, Dewi K.; Ounchanum, Pradthana; Puthanakit, Thanyawee; Sudjaritruk, Tavitiya; et al.
Abstract : Objective: To implement a standardized cause of death reporting and review process to systematically disaggregate causes of HIV-related deaths in a cohort of Asian children and adolescents. Design: Death-related data were retrospectively and prospectively assessed in a longitudinal regional cohort study. Methods: Children under routine HIV care at sites in Cambodia, India, Indonesia, Malaysia, Thailand, and Vietnam between 2008 and 2017 were followed. Causes of death were reported and then independently and centrally reviewed. Predictors were compared using competing risks survival regression analyses. Results: Among 5918 children, 5523 (93%; 52% male) had ever been on combination antiretroviral therapy. Of 371 (6.3%) deaths, 312 (84%) occurred in those with a history of combination antiretroviral therapy (crude all-cause mortality 9.6 per 1000 person-years; total follow-up time 32 361 person-years). In this group, median age at death was 7.0 (2.9–13) years; median CD4 + cell count was 73 (16–325) cells/μl. The most common underlying causes of death were pneumonia due to unspecified pathogens (17%), tuberculosis (16%), sepsis (8.0%), and AIDS (6.7%); 12% of causes were unknown. These clinical diagnoses were further grouped into AIDS-related infections (22%) and noninfections (5.8%), and non-AIDS-related infections (47%) and noninfections (11%); with 12% unknown, 2.2% not reviewed. Higher CD4 + cell count and better weight-for-age z -score were protective against death. Conclusion: Our standardized cause of death assessment provides robust data to inform regional resource allocation for pediatric diagnostic evaluations and prioritization of clinical interventions, and highlight the continued importance of opportunistic and nonopportunistic infections as causes of death in our cohort. Abstract : Supplemental Digital Content is available in the text